Effect of smear layer deproteinization on bonding of self-etch adhesives to dentin: a systematic review and meta-analysis - Khaldoan H. Alshaikh; Hamdi H. H. Hamama; Salah H. Mahmoud (Restorative Dentistry & Endodontics, 2018)
ObjectivesThe aim of this systematic review was to critically analyze previously published studies of the effects of dentin surface pretreatment with deproteinizing agents on the bonding of self-etch (SE) adhesives to dentin. Additionally, a meta-analysis was conducted to quantify the effects of the above-mentioned surface pretreatment methods on the bonding of SE adhesives to dentin.Materials and MethodsAn electronic search was performed using the following databases: Scopus, PubMed and ScienceDirect. The online search was performed using the following keywords: ‘dentin’ or ‘hypochlorous acid’ or ‘sodium hypochlorite’ and ‘self-etch adhesive.’ The following categories were excluded during the assessment process: non-English articles, randomized clinical trials, case reports, animal studies, and review articles. The reviewed studies were subjected to meta-analysis to quantify the effect of the application time and concentration of sodium hypochlorite (NaOCl) and hypochlorous acid (HOCl) deproteinizing agents on bonding to dentin.ResultsOnly 9 laboratory studies fit the inclusion criteria of this systematic review. The results of the meta-analysis revealed that the pooled average microtensile bond strength values to dentin pre-treated with deproteinizing agents (15.71 MPa) was significantly lower than those of the non-treated control group (20.94 MPa).ConclusionsIn light of the currently available scientific evidence, dentin surface pretreatment with deproteinizing agents does not enhance the bonding of SE adhesives to dentin. The HOCl deproteinizing agent exhibited minimal adverse effects on bonding to dentin in comparison with NaOCl solutions.